2020
DOI: 10.1093/rheumatology/keaa127
|View full text |Cite
|
Sign up to set email alerts
|

Older age onset of systemic sclerosis – accelerated disease progression in all disease subsets

Abstract: Objectives Systemic sclerosis is a heterogeneous, multisystem disease. It can occur at any age, but most patients develop the disease between the age of 40 to 50 years. There is controversial evidence on whether/how the age at disease onset affects their clinical phenotype. We here investigate the relationship between age at disease onset and symptoms in a large cohort of SSc patients (lcSSc, dcSSc and SSc-overlap syndromes). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
5
15
1
Order By: Relevance
“…PYLL have been found to be higher in SSc than in other autoimmune disorders such as rheumatoid arthritis 23 . In our study, rates for women were higher than for men, in contrast to previous studies 17,24 …”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…PYLL have been found to be higher in SSc than in other autoimmune disorders such as rheumatoid arthritis 23 . In our study, rates for women were higher than for men, in contrast to previous studies 17,24 …”
Section: Discussioncontrasting
confidence: 95%
“…23 In our study, rates for women were higher than for men, in contrast to previous studies. 17,24 We hypothesize that the falling trend recorded in younger cohorts from 1990 might indicate a stabilization of the Spanish mortality rates of SSc. This is supported by previous studies, which have shown that, despite SSc mortality overtaking mortality of the general population, trends have been falling in the past decades.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has also served to immunologically characterize German patients on a national level 21 . It has also deepened the knowledge and prognostic evaluation of patients with overlap syndrome 22 and late-onset SSc 23 and the excessive use of corticosteroids and immunosuppressants in patients with SSc 24 .…”
Section: Germany 2003mentioning
confidence: 99%